Impact of reimbursement program "Аffordable Medicines" on consumptiom of betablockers in Ukraine in 2017-2020 - Anton Gonchar; Natalia Sholoiko (Bogomolets National Medical University, 2022)
the article presents the results of the study of impact of the reimbursement program "Affordable medicines" on consumption of beta-blockers in Ukraine, used for treatment of cardiovascular diseases. Analysis was conducted based on analytical data of Ukrainian pharmaceutical market research system "PharmXplorer" of the company "Proxima Research", with current legislation taken into account. It was estimated, that in 2021, according to international non-proprietary name and 5th level of ATC classification -  two non-selective beta-blockers: propanolol (ATC code  С07АА05) and sotalol (С07АА07); six selective beta-blockers: metoprolol (С07АВ02), atenolol (С07АВ03), betaxolol (С07АВ05), bisoprolol (С07АВ07), esmolol (С07АВ09) and nebivolol (С07АВ12); and one beta-blocker from alpha and beta blocking agents group - carvedilol (C07GA02) are allowed for medical use in Ukraine. From the beginning, when reimbursement program "Affordable medicines" was implemented (April 1st, 2017), only 4 beta-blockers were included in the reimbursement list. Consumption patterns were analyzed in terms of defined daily dose, and it was estimated that bisoprolol was the leader among all beta-blockers in terms of consumption in period from 2016 to 2020. The findings show, that among beta-blockers, that were included in the reimbursement list, the major annual growth of consumption was detected for bisoprolol and carvedilol, although the growth of consumption of metoprolol and atenolol was noted only within the first year of functioning of the reimbursement program "Affordable medicines", and beginning from 2018, the consumption of these two beta-blockers was declining annually.  Among beta-blockers, that were not included in the reimbursement list, the increase in annual growth of consumption was spotted for nebivolol and sotalol. DDD/1000 inhabitants/day indicators were calculated for each beta-blocker. It was found, that throughout the years the biggest value of this indicator was for bisoprolol - 8,46 in 2016; 11,74 in 2017; 15,28 in 2018 ; 16,88 and 17,48 in 2019 and in 2020 respectfully. The growth of this indicator can give evidence about positive effect of the reimbursement program "Affordable medicines" on consumption of bisoprolol and its affordability for population in Ukraine in 2017-2020.